Resilience Index and Non-Structural Mitigation in Facing Earthquakes in Bantul Regency - Andikasari, Lian Yuanita; Riyandari, Ritha; Qonita, Zulfa; Utami, Dyah Nursita (Geosfera Indonesia, 2025)
Bantul is one of the regencies in the Special Region of Yogyakarta that was affected by the damage, losses, and casualties due to the Yogyakarta earthquake disaster in 2006. The current condition with the potential for a Megathrust earthquake in the South of Java Island is a special concern in determining the resilience of an area, determining what needs to be improved in preparedness, and providing alternative non-structural mitigation that can be carried out in dealing with earthquakes. This study was conducted to determine the resilience index in social and economic aspects which were then described into six derivative variables. The method used in this study uses literature studies and sequential data analysis. Secondary data is used to calculate the resilience index with predetermined weightings. The results showed that the resilience index in 2021, 2022, and 2023 in the social aspects of 0.985, 0.981, and 0.979 and economic aspects of 1.05, 1.08, and 1.06. During these three years, the index resilience of the social aspect has decreased so mitigation was needed to increase social aspect resilience and prepare the community to face earthquake disasters. One of the non-structural mitigation efforts that can be done is by providing education or training. The economic aspect also needs to be improved with several non-structural mitigation alternatives such as increasing and creating jobs and developing micro, small, and medium enterprises by maximizing the potential of local resources.